Socioeconomic inequalities in the risk of suicide attempts among sexual minority adolescents: Findings from the UK's Millennium Cohort StudyResearch in context - James White; Sophie Borgia; David H. Rehkopf (Elsevier, 2023)
Summary: Background: Both sexual minority and socioeconomically deprived young people are at an increased risk of making a suicide attempt. Intersectionality theory predicts these risk factors will interact synergistically to create unique vulnerabilities. We investigated the risk of suicide attempts in sexual minority socioeconomically deprived young people in a contemporary national cohort. Methods: The Millennium Cohort Study (MCS) is a birth cohort study in the UK following children born 2000-2002. Children in the MCS have been followed up over seven sweeps to date at ages 9 months, 3, 5, 7, 11, 14 and 17 years. The relative risk (RR) of self-reported suicide attempts at 17 years by sexual minority status and parental unemployment was estimated using multivariable log-binomial regression. Additive interaction, representing the synergistic effect, was estimated using the relative excess risk due to interaction (RERI). Findings: Between January, 2018 and March, 2019, 10,247 adolescents provided their sexuality and parents their employment status. 758 (7.4%) of 10,247 adolescents had made a suicide attempt. Relative to heterosexual young people living with no unemployed parents, the RR for sexual minorities living with no unemployed parents/carers was 2.93 (95% CI 2.26-3.79), one unemployed was 4.46 (95% CI 2.94-6.77), and two was 6.35 (95% CI 3.62-11.14). There was evidence of a positive additive interaction. The RERI for having one unemployed parent was 1.08 (95% CI −0.54 to 2.69) and two was 3.10 (95% CI −1.58 to 7.78). Sensitivity analyses using housing tenure and in a sample with no missing data generated comparable results. Interpretation: To our knowledge, this is the first evidence that socioeconomically deprived sexual minority adolescents are uniquely vulnerable to making a suicide attempt. Health and educational practitioners need to be aware of the increased risk of suicide attempts in socioeconomically deprived sexual minority adolescents. Funding: Economic and Social Research Council (ESRC).